Makna Dibalik Cover Majalah Tempo Edisi Aib Anggaran Anies - Nur Afandi (Al-MUNZIR, 2023)
This research aims to determine the meaning behind the cover of the 11-17 November 2019 issue of Tempo magazine with the main title "Anies' Budget Disgrace", which includes a caricature of one of the national figures, so as not to cause wild opinions and noise in the community. This research uses a qualitative approach method that produces descriptive data, with primary data obtained from the documentation of Tempo magazine and secondary data obtained from relevant literature and journals. The collected data is then analysed using Charles Sanders Pierce's semiotics with its trichotomous concept. The results of this study show that Tempo magazine has fulfilled its function of social control and is directly involved in monitoring issues of public interest. The caricature of Anies, depicted by Tempo as trapped in DKI Jakarta's budgeting system, is depicted as falling into a can of glue. The can is a packet of Aica-Aibon glue, which is believed to be one of the budget items with a fantastic purchase value.Keywords: controversy, cover magazine; semiotics; tempo